Ecological approach and fairy-tales: study with infant victims - Alves, Heliana Castro; Emmel, Maria Luisa Guillaumon (Paidéia (Ribeirão Preto), 2008)
This study was carried out with a group of children, victims of domestic violence, based on the ecological perspective of multi-factorial analysis of the domestic violence phenomenon and theories that consider the importance of Fairy Tales in children's emotional development. The objectives were to describe the impact of Fairy Tales in the emergence of latent emotional content from playful actions; set considerations on the context in which the child is raised from an ecological perspective regarding the phenomenon. Semi-structured interviews were carried out with the children's parents and interventions with the group, sessions of storytelling and symbolic activities, were developed. The research results appoint to the familiar micro-system, exosystem, mesosystem and macro-system as risk factors for domestic violence. The compiled data suggest that oral narratives can work as a support, gathering a repertory of elements that awakes in children content related to their personal experiences.